Do Oral Probiotics Affect Growth and Neurodevelopmental Outcomes in Very Low-Birth-Weight Preterm Infants? - Sari, Fatma Nur; Eras, Zeynep; Dizdar, Evrim Alyamac; Erdeve, Omer; Oguz, Serife Suna; Uras, Nurdan; Dilmen, Ugur (American Journal of Perinatology, 2012)
Objective To evaluate the growth and neurodevelopment outcomes of very low-birth-weight (VLBW) preterm infants supplemented with oral probiotics for the prevention of necrotizing enterocolitis (NEC).Study Design This prospective follow-up study was conducted in a cohort of VLBW preterm infants enrolled in a randomized controlled clinical trial to evaluate the efficacy of oral probiotics for the prevention of NEC. Growth outcomes included weight, length, and head circumference. Cognitive and neuromotor development were assessed by using the Bayley Scales of Infant Development II. Sensory and neurological performance was evaluated by standard techniques. The primary outcome was neurodevelopmental impairment at 18 to 22 months' corrected age.Results A total of 221 infants completed the trial protocol. Of the 208 infants eligible for follow-up, 174 infants (86 in the probiotics group and 88 in the control group) were evaluated. There was no significant difference in growth and neurodevelopmental outcomes between the two groups.Conclusion Oral probiotic administered to VLBW infants to reduce the incidence and severity of NEC started with the first feed did not affect growth, neuromotor, neurosensory, and cognitive outcomes at 18 to 22 months' corrected age.
Keywords: growth; neurodevelopment; preterm infant; probiotics